The Role of Organizational Agility in improving the Quality of work life of Government Hospitals – A field study on the administrative staff at the Children’s Hospital in Taif Governorate – - Alotaibi, Sarah Aziz (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aimed to explore the role of organizational agility in improving the quality of functional life in government hospitals, the case of Children’s Hospital in Taif. The study examined the effect of organizational agility represented in: (sensing agility, decision-making agility, application agility) in improving the job quality at work. In order to achieve these objectives, the study adopted descriptive analytical method, and the study used the questionnaire as a tool for data collection and a total of 102 questionnaires were analysed. The findings of the study showed that there was a positive direct and strong correlation between organizational agility and job quality at a significance level of (p≤ α 0.05). Furthermore, the dimension of decision-making agility has the greatest impact on improving job quality. The results of this study will guide healthcare institutions and policy makers to develop quick and proactive flexible plans that meet the needs of employees to face environmental changes.